Manifestasi Klinis dan Perjalanan Penyakit pada Pasien Covid-19 - Celine Grace (MAJORITY, 2020)
SARS-CoV-2 or nCov-19 is included in the category betaCoVs the genomic analysis suggests that SARS-CoV-2 may evolve that are found on bats. Because mutations in the original strains can be directly triggered virulence towards humans. According to the World Health Organization (WHO), the viral disease continues to emerge and is a serious problem for public health. In the last twenty years, several viral epidemics such as severe coronavirus acute respiratory syndrome (SARS-CoV) at 2002 to 2003. It was found that 98% of patients in their study had a fever, which 78% had temperatures higher than 38 °c. They reported that 76% of patients had coughed, 44% of patients experienced fatigue and muscular pain, and 55% of patients experienced dyspnea with old age cases and the owners of Compenion and ARDS would have worse prognosis when infected with this virus. With the absence of effective treatment, the best way to handle the epidemic of SARS-CoV-2 is to control the source of infection. Strategies include early diagnosis, isolation, and supportive care. Immunosuppressive drugs have an effect on humoral immunity, cell-mediated immunity and neutrophil function, increasing the risk of severe infections caused by viral agents. Patients receiving immunosuppressive therapy are at risk to have a more severe manifestation of the viral infection. Some studies also included chloroquine as a treatment of Cov-19.